Implementation of Loosepart Media in Developing Children's Creativity - Lestari, Retno Triwahyuning; Priyanti, Nita (Kirana Publisher (KNPub), 2024)
This qualitative-based research focuses on the narrative and linguistic representation of specific situations or phenomena in a natural context, using a variety of data-gathering techniques that do not alter the research environment. A qualitative descriptive method was applied to describe the use of loose media in sharpening early childhood creativity at Islamic School Al Azhar 12 Cikarang by collecting information through narration. In the study on the application of loose parts to stimulate creativity in children at an early age, conducted at Islamic School Al Azhar 12, information was obtained through the involvement of 24 individuals, consisting of a class teacher and 23 students from Class A Shafa, in the institution. The use of media loose Part in Islamic school Al Azhar 12 Cikarang proved to be effective in stimulating the development of creativity in early children through a structured series of activities. This includes the steps taken by children as well as the approach adopted by educators. Exploration activities involving a variety of elements in the learning environment attracted great interest from children